Optimization of Vagal Stimulation Protocol Based on Spontaneous Breathing Rate - De Souza, Liliane Appratto; Ferreira, Janaina Barcellos; Schein, Andressa Silveira de Oliveira; Dartora, Daniela Ravizzoni; Casali, Adenauer Girardi; Scassola, Catharina M. Carvalho; Tobaldini, Eleonora; Montano, Nicola; Guzzetti, Stefano; Porta, Alberto; Irigoyen, Maria Claudia; Casali, Karina Rabello (Frontiers in Physiology, 2018)
Controlled breathing maneuver is being widely applied for cardiovascular autonomic control evaluation and cardiac vagal activation through reduction of breathing rate (BR). However, this maneuver presented contradictory results depending on the protocol and the chosen BR. These variations may be related to the individual intrinsic profile baseline sympathetic tonus, as described before by others. In this study, we evaluated the effect of controlled breathing maneuver on cardiovascular autonomic control in 26 healthy subjects allocated into two protocols: 1) controlled breathing in three different rates (10, 15 and 20 breaths/min) and 2) controlled breathing in rates normalized by the individual spontaneous breathing rate (SBR) at 100%, 80%, 70% and 50%. Our results showed autonomic responses favorable to vagal modulation with the lower BR maneuvers. Nevertheless, while this activation was variable using the standard protocol, all participants of the normalized protocol demonstrated an increase of vagal modulation at 80% BR (HFnu 80%= 67.5% vs 48.2%, p<0.0001). These results suggest that controlled breathing protocols to induce vagal activation should consider the SBR, being limited to values moderately lower than the baseline.